Inspirasi Alquran dan Hadis dalam Menyikapi Informasi Hoax - Stepanus Sigit Pranoto (AL QUDS : Jurnal Studi Alquran dan Hadis, 2018)
The rapid growth of hoax information dissemination through social media is increasingly unstoppable. One of the causes is the narcissistic behavior that exists within the users of social media. This article explains the narcissistic behavior that has become a fertile ground for the dissemination of hoax information and how to overcome it by taking inspiration from the Qur'an and Hadith. This research uses qualitative design and literature research approach. Meanwhile, the determination of the verses of Al-Qur'an in this study used Tafsir Maudhu'i method. Based on the Qur'an and Hadith, this study shows that in an effort to prevent the widespread of hoax information, one needs to be critical and wise in using social media, as well as doing tabayyun before sharing any information.